PNA C-C+ i-motif: superior stability of PNA TC8 tetraplexes compared to DNA TC8 tetraplexes at low pH - Sharma, NK; Ganesh, Krishna N. (Chemical Communications, 2005)
Study of self-assembly of PNA TC8 monitored by UV thermal transition at 295 nm indicates formation of a C-C+ tetraplex (i-motif) in acidic pH, with higher stability than the analogous dTC(8).